Hazard analysis techniques for system safety - Ericson, Clifton A., ....- (Hoboken : Wiley-Interscience, 2005)
Written by a former President of the System Safety Society and winner of the Boeing Achievement and Apollo awards for his safety analysis work, Hazard Analysis Techniques for System Safety explains, in detail, how to perform the most commonly used hazard analysis techniques employed by the system safety engineering discipline. The book also explains when and why to use each technique with sufficient detail and examples to make techniques easily understood and performed by readers. The first book to provide enough information for a reader to adequately perform the technique without additional training, Hazard Analysis Techniques for System Safety is not overly technical, and can be easily understood by readers with a minimal amount of technical background.
Keywords: Techniek ; veiligheid